Aging assessment method of oil–paper composite insulation based on repeated polarization current characteristics. Issue 1 (12th October 2021) - Zhuang, Yu; Wang, Yonghong; Wang, Meiying; Wei, Xinlao
Abstract: To explore the aging assessment method of the oil–paper insulation in power transformers, the polarization and depolarization current (PDC) characteristics of oil–paper composite insulation samples are investigated under high applied voltage. Based on the asymmetry of polarization absorption current and depolarization current and the polarity effect of insulation pressboard, the repeated polarization current test method is proposed. A novel aging characteristic parameter, which is the ratio of the normalized charge for the first polarization and the normalized charge for the second polarization, is extracted. The difference between the decay rates of the first polarization current and the second polarization current increases at first and then decreases with the polarization time, and decreases with increasing aging degree of the pressboard. The more serious the insulation aging is, the smaller the variation range of aging characteristic parameter with polarization time is, and the closer the value is to 1. With decrease in the DP, the maximum of aging characteristic parameter changes in a decreasing trend. The aging condition of the oil–paper composite insulation can be assessed by the repeated polarization current method and the relationship between the aging characteristic parameter and the polarization time.